A new approach to agroclimatic classification to find out crop potential (MAUSAM, 1988)
Agroclimatic classification using appropriate climatic parameters can be a very useful tool to identify crop potential of a region. There may be different approaches of classification and the adequacy of an approach depends on ultimate objectives. In this paper, a theory has been developed for agroclimatic classification on the basis of an index called Moisture Availability Index (MAl) which is defined as the ratio of weekly assured rainfall and potential evapotranspiration. In this classification, MAl on weekly basis and different values of MAI appropriate to various pheno-phases have been taken into account. The classification has been made on the basis of moisture availability index at 50% level. However, duration of the crop growing period has also been discussed at other levels.Following this methodology, the part of the India, where annual rainfall is more than 400 mm; has been divided into 7 broad agroclimatic zones. The arid region has been divided into three zones on the basis of moisture availability index at 30% level. The theory has been applied to the dry farming tract of Maharashtra taking micro-level data. This indicates that while a macro-scale study can give some broad aspects of crop potential, it is necessary to do micro-level analysis so that specific areas of varying crop potential can be pin-pointed and appropriate recommendation can be drawn up.